Radio Frequency Identification from the viewpoint of students of computer science - Hoffmann, Miklós; Juhász, Tibor; Taskó, Tünde (Teaching Mathematics and Computer Science, 2014)
This paper aims at creating the right pedagogical attitudes in term of teaching a new technology, Radio Frequency Identification (RFID) by evaluating the social acceptance of this new method. Survey of future teachers, students of teacher master studies and students from informatics oriented secondary schools were surveyed comparing their attitudes in terms of RFID to other recent technologies. Consequences of this survey are incorporated into the curriculum of the new RFID course at our institution.